Metodologia de controle Volt/Var coordenado para redes de distribuição a partir de lógica heurística - Biazzi, Roberta Razzolini (2019)
The reactive power management and voltage control enable voltage profile improvements. Maintain the voltage value within the appropriate ranges requires efficient techniques that consider joint and coordinated operation between reactive power devices and voltage regulating equipment. These techniques are referenced in the literature as Volt/Var Control (VVC). The main objective of this work is to develop a centralized volt/var control methodology that acts on regulators transformers, capacitor banks and photovoltaic smart inverters. The optimization technique is based on heuristic algorithm and works with the effectiveness of the control equipment to reduce the electrical power losses. The methodology was implement from the software OpenDSS e MATLAB. The control was applied in distribution test systems and in the UFSM network, where all result was satisfactory and met the quality and reliability requirements of the systems. The result of the same networks simulated by traditional controls were not promising, this fact reiterates the contributions of this work on volt/var control studies.